Judul Analisis Risiko Kerja pada Area Workshop Hydraulic dengan Metode HIRA (Hazard Identification and Risk Assesment) di PT. XYZ - Muhamad Bob Anthony (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Workshop PT. XYZ is a part of a company that carries out activities in the field of maintenance and repair, especially hydraulic, pneumatic and lubrication equipment. These workshop activities include welding activities, operating machine tools and other mechanical work. This study aims to determine the value of the potential risk of occupational hazards and the level of risk of potential occupational hazards at PT. XYZ in the workshop area. This study uses an approach with the HIRA (Hazard Identification and Risk Assessment) method to determine the value of the risk of occupational hazards and the level of risk of potential occupational hazards. The results obtained by using HIRA (hazard identification and risk assessment) were obtained as many as 29 risks which were classified based on potential hazards, namely 28% extreme risk, 41% high risk, moderate risk of 31% and there is no low risk. Improvement recommendations are made based on the level of extreme risk (extreme risk) and high risk (high risk) to prevent and reduce the level of risk of work accidents in the workshop area, while for the moderate risk level, the mitigation recommendation is to supervise the work and make an SWI (simplified working instruction) to make it easier for workers to understand safe and correct work procedures.